Author Correction: Ecological effects of full and partial protection in the crowded Mediterranean Sea: a regional meta-analysis. Issue 1 (December 2018) - Giakoumi, Sylvaine; Scianna, Claudia; Plass-Johnson, Jeremiah; Micheli, Fiorenza; Grorud-Colvert, Kirsten; Thiriet, Pierre; Claudet, Joachim; Carlo, Giuseppe; Franco, Antonio; Gaines, Steven; García-Charton, José; Lubchenco, Jane; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.